Mother and calf humpback whale responses to vessels around the Abrolhos Archipelago, Bahia, Brazil - Morete, Maria E.; Bisi, Tatiana L.; Rosso, Sergio (J. Cetacean Res. Manage., 2023)
As the humpback whale population spreads along the Brazilian coast, whalewatching activities are becoming more frequent especially along the coast of the state of Bahia. In order to evaluate the appropriateness of the Brazilian legislation that regulates vessel approaches to cetaceans, the behaviour of humpback whale mothers and calves was studied around the Abrolhos Archipelago, an area with a high concentration of tourism vessels. Mother and calf groups were observed by means of continuous sampling and tracked along with vessels using a theodolite. Three whale-vessel categories of distances were analysed: closer than 100m (category 1); between 100-300m (category 2); and further than 300m (category 3). Rates of behavioural events and time spent in particular behavioural states of mothers and calves were compared separately in the three categories to observations of randomly selected mother and calf groups not involved in an interaction with a vessel (category 0). A total effort of 39hr was analysed including observations in each of the four categories. The results showed that differences in humpback whale mother and calf behaviour occurred mostly in the presence of vessels within distances of 100-300m. Mothers increased linearity and mean speed of movement, decreased blow intervals and time spent resting. Calves exhibited less rolling, fluke-ups and others active behavioural events, as well as diminished resting time. During interaction with vessels, the frequency of potentially important behaviours, both for mothers and calves, reduced, probably as a response to the approaching whalewatching vessels. Repeated short-term behavioural disturbances might lead to cumulative effects that may result in risks for species conservation. It is recommended that the Brazilian legislation should include a 300m-radius restrictive zone around mother and calf groups or include a 300m caution zone, where boats should reduce speed and avoid sudden changes in engine status and direction. The environmental education work with local communities along the coast must be continued and constant.